AMICA: An Adaptive Mobile Application for the Learning of Academic English with Pedagogical Agents - Chuah, Kee Man; Muhammad Kamarul, Kabilan (2022)
The mastery of academic English at tertiary levels is undeniably pivotal in ensuring students’ progress and success. Its importance is due to the number of academic materials that students need to refer to and they are largely published in English. In teaching academic English, however, lecturers tend to face problems in providing sustainable guidance and meaningful feedback to the students. Hence, this project proposes a viable solution by introducing a mobile application that could be used to as a tool for students to independently learn academic English. The Adaptive Mobile Interactive Coach for Academic English (or known as AMICA) is a mobile application equipped with interactive pedagogical agents that would constantly guide students in academic reading and writing. In the reading module, they would be able to learn the proper strategies to read journal papers and academic materials through the adaptive and interactive assistance provided by the virtual agent or coach. As for the writing module, they would be able to obtain feedback from the AMICA app on the more accurate way of expressing ideas academically, especially in terms of using academic words and sentence structure. The AMICA app has been piloted on 35 undergraduate students and the outcomes from the test are encouraging. A majority of the students considered it as effective since they treat it like a virtual friend that guides them without the need to disturb their lecturers constantly. It also motivates them to master academic English as the AMICA app was designed to be engaging and interesting rather than the typical lecture-style delivery of the subject. Further improvements will be made to the AMICA app before it is publicly released.